A systematic study of the impact of additives on structural and mechanical properties of Magnetorheological fluids. (2021) - Gopinath, B.; Sathishkumar, G.K.; Karthik, P.; Martin Charles, M.; Ashok, K.G.; Ibrahim, Mohamed; Mohamed Akheel, M.
Abstract: Magneto rheological fluids, often called smart fluids, play a significant role in effective mechanical braking systems, haptic devices, mechanical dampers and other mechanical devices. Presently, the properties of Magneto rheological fluids added with additives or nanoparticles were discussed. The introduction of an additive/nanoparticle in MR fluid alters the mechanical, thermal, structural and other properties of the fluid. The characteristic feature of this fluid is that they become solidified under the effect of an applied magnetic field. This is mainly due to the chain development of suspended molecules in the fluid medium. When these fluids are mixed with nanoparticle additives, these chain forms become stronger, as the nanoparticles occupy the spaces among the molecules of MR fluid. This in turn increases the dispersion stability, yielding strength of the fluid under action. Due to higher solubility of suspended iron particles, the Carbonyl Iron based MR fluid is the most commonly used MR fluid.